The Use of Task-Based Language Teaching in Improving Students' Writing Skills at X Grade in SMK Muhammadiyah 2 Bontoala - Nurhidayah J, Israwati; Prabawati Rum, Eka; Hambali, Uyunnasirah (Journal of Language Testing and Assessment, 2023)
This study aimed to find out whether or not Task-Based Language Teaching method improve the writing skills of class X AP students at SMK Muhammadiyah 2 Bontoala in terms of grammar and mechanics. The research method used was quantitative with a pre-experimental design. The population in this study were students of SMK Muhammadiyah 2 Bontoala. The number of samples used was 20 students and the sample class were selected using a purposive sampling technique.Based on the results, the pre-test score of students' writing skills in terms of grammar was 65.8 and the post-test score was 81.4. While the Pre-test score of students' skills in terms of mechanics was 64.0 and post-test is 83.0. After analyzed the results of the pre-test and post-test data, the researcher found that in writing skills, p-value (0.000) less than α (0.05), this indicates that the null hypothesis is rejected and alternative hypothesis is accepted.The researcher concluded that Task-Based Language Teaching through descriptive text at SMK Muhammadiyah 2 Bontoala improved students' writing skills. There is a significant difference in students' writing skills in terms of grammar and mechanics with the use of Task-Based Language Teaching methods.